A comparative review of the national innovation framework in Africa: case study of Mauritius and South Africa - Roopchund, Randhir (Management and Entrepreneurship: Trends of Development, 2025)
The current study analyses the National Innovation Frameworks adopted by two strong African economies, namely Mauritius and South Africa. These frameworks have been strategically developed to boost economic growth by fostering a culture rooted in innovation, creativity, and excellence. Recognising the increasing importance of knowledge-based economies, both countries have sought to position innovation at the core of their development agenda, ensuring long-term competitiveness in a globalised world. The study goes beyond a descriptive comparison by critically examining the overall justification for engaging in such innovation frameworks. It explores how innovation contributes not only to economic performance but also to addressing broader societal challenges such as employment creation, social inclusion, and sustainable development. In addition, the research develops a clear understanding of the contextual differences in the design and implementation of innovation approaches in Mauritius and South Africa, recognising that unique historical, institutional, and economic contexts influence their policy priorities and execution. A qualitative research approach is adopted, using a multi-case study method supported by directed content analysis. This methodology enables a systematic and in-depth exploration of the similarities and contrasts between the two national frameworks. The findings are highly relevant to policymakers, practitioners, and academics, as they shed light on the innovation pathways, drivers, and influences that can enhance economic growth and national resilience. The study also highlights the value of innovation-led strategies in enabling African economies to move up the global value chain and sustain long-term development. JEL Classification: O31, O32, O38, O57